Gambaran status gizi pada diabetes melitus - Syamsu, Rachmat Faisal; Amrin, Alisa Febriana; Saad, Lucky Amelia (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Type 2 diabetes mellitus is a public health problem with a steadily increasing prevalence and is closely related to nutritional status. Nutritional imbalances, both undernutrition and overnutrition, impact glycemic control and the risk of complications. Purpose: To determine the nutritional status of type 2 diabetes mellitus patients based on Body Mass Index (BMI). Method: This is a descriptive study using a secondary data approach. Samples were taken using a total sampling technique from all type 2 diabetes mellitus patients registered in the medical records of the Maccini Sawah Community Health Center during the period October–November 2025. Nutritional status data was determined based on BMI calculations and classified according to WHO criteria. Results: A total of 37 type 2 diabetes mellitus patients were studied, the majority of whom had normal nutritional status (35.14%). Overweight patients accounted for 27.03%, class I obesity for 24.32%, and class II obesity for 5.41%. Meanwhile, 8.11% of patients were underweight. Conclusion: The description of the nutritional status of type 2 diabetes mellitus patients shows that more than half of the patients are overweight and obese. Keywords: Body Mass Index; Nutritional Status; Primary Health Care; Type 2 Diabetes Mellitus. Pendahuluan: Diabetes melitus tipe 2 merupakan masalah kesehatan masyarakat dengan prevalensi yang terus meningkat dan sangat berkaitan dengan status gizi. Ketidakseimbangan status gizi, baik gizi kurang maupun gizi lebih, berpengaruh terhadap kontrol glikemik dan risiko komplikasi. Tujuan: Untuk mengetahui gambaran status gizi pasien diabetes melitus tipe 2 berdasarkan Indeks Massa Tubuh (IMT). Metode: Penelitian ini merupakan penelitian deskriptif dengan pendekatan data sekunder. Sampel diambil menggunakan teknik total sampling terhadap seluruh pasien diabetes melitus tipe 2 yang tercatat dalam rekam medis Puskesmas Maccini Sawah pada periode Oktober–November 2025. Data status gizi ditentukan berdasarkan perhitungan IMT dan diklasifikasikan menurut kriteria WHO. Hasil: Sebanyak 37 pasien diabetes melitus tipe 2 yang diteliti, sebagian besar memiliki status gizi normal (35.14%). Pasien dengan status overweight ditemukan sebesar 27.03%, obesitas kelas I sebesar 24.32%, dan obesitas kelas II sebesar 5.41%. Sementara itu, 8.11% pasien berada dalam kategori underweight. Simpulan: Gambaran status gizi pasien diabetes melitus tipe 2 menunjukkan bahwa lebih dari separuh pasien mengalami kelebihan berat badan dan obesitas. Kata Kunci: Diabetes Melitus Tipe 2; Indeks Massa Tubuh; Puskesmas; Status Gizi.